2021
DOI: 10.1038/s41380-021-01282-z
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the m6A brain methylome by ALKBH5-mediated demethylation: a new contender for synaptic tagging

Abstract: Synaptic plasticity processes, which underlie learning and memory formation, require RNA to be translated local to synapses. The synaptic tagging hypothesis has previously been proposed to explain how mRNAs are available at specific activated synapses. However how RNA is regulated, and which transcripts are silenced or processed as part of the tagging process is still unknown. Modification of RNA by N6-methyladenosine (m6A/m) influences the cellular fate of mRNA. Here, by advanced microscopy, we showed that m6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 82 publications
(134 reference statements)
1
23
0
Order By: Relevance
“…We also compared the methylated transcripts between the ACC and the hippocampus, two more distantly related brain regions at the structural and functional level, and observed that 61% of the m 6 A transcript could be detected in both brain regions. These results go in accordance with previously published data that reported a considerable amount of tissue specificity in the populations of transcripts that are labeled by m 6 A 23 54 53 . While noticeable difference in the m 6 A landscape were detected between brain subregions, the location of m 6 A marks were mostly identical within all hippocampal regions and the ACC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also compared the methylated transcripts between the ACC and the hippocampus, two more distantly related brain regions at the structural and functional level, and observed that 61% of the m 6 A transcript could be detected in both brain regions. These results go in accordance with previously published data that reported a considerable amount of tissue specificity in the populations of transcripts that are labeled by m 6 A 23 54 53 . While noticeable difference in the m 6 A landscape were detected between brain subregions, the location of m 6 A marks were mostly identical within all hippocampal regions and the ACC.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the knockdowns of Ythdf1 negatively affects spine formation, long-term potentiation, and learning in a hippocampus-dependent manner 26 28 . More recently, the m 6 A reader YTHDF3 as well as the eraser ALKBH5 have also been linked to the regulation of m 6 A at the synapse, further increasing the possibilities for regulation in such compartments 54 . Of course, other m6A reader may also play a role in regulating synaptic mRNA translation directly or indirectly, via processes like degradation, transport or phase separation 31 32 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, we found that mRNA methylation was actively regulated in the dorsal hippocampus of both WT and Hdh + /Q111 mice in response to spatial learning, though a different m6A pattern was observed in the transcriptome of Hdh + /Q111 mice when compared to WT mice. Thus, although both genotypes showed similar methylation in IEGs and synaptic genes known to be target of m6A modifications [ 39 , 76 , 89 , 90 ], Hdh + /Q111 mice failed to increase methylation or induced demethylation of some synaptic genes critical for proper learning. Since an increase of m6A in the mouse hippocampus or prefrontal cortex in response to learning has been associated with the constrain of the sorting efficiencies or turnover of nascent RNAs, the reduced m6A methylation observed in Hdh + /Q111 hippocampus could indicate that the degradation and stability of several synaptic genes is affected in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that ALKBH5 protein decreased in 3d group but increased in 7d group, suggesting that it could be one of the potential targets for treatment of stroke, and increases in demethylase may improve cerebral infarction by changing the m 6 A modification. Additionally, YTHDF3 also showed the same trend as ALKBH5, and the latest study showed that YTHDF3 and ALKBH5 were involved in synaptic plasticity (Martinez De La Cruz et al, 2021 ). However, the specific mechanisms require further study.…”
Section: Discussionmentioning
confidence: 87%